Reliability Evaluation Method for Electricity Meters with Competitive Failures Under Arid High Temperature - ZHANG Wei; LI Ning; CHEN Min; HE Shuai (Journal of Harbin University of Science and Technology)
How to carry out the research on the life and reliability of smart electricity meters (SEMs) with the help of typical environmental test bases is a hot and challenging issue in the current industry. In view of the problems of a small amount of failure time, sudden failure and degradation failure of SEMs in the typical environment test base of high dry heat, the classical and Bayes evaluation methods of SEMs reliability are constructed considering the random truncation of the fault data. The reliability information of SEMs in the field operation is combined with the reliability information of SEMs in the typical environment test base of high dry heat to expand the information content and improve the accuracy of SEMs reliability evaluation. Further, considering the multi-index and degradation failure of the metering performance of SEMs, a comprehensive evaluation method of the reliability of SEMs is constructed based on the multivariate Wiener process with competitive failure modes under high dry heat environment, and the point estimates and confidence limits of the three reliability indicators of SEMs are given, including reliability, MTBF and reliable life. The on-site grid- connected operational data from Turpan, Urumqi, and Altay regions in Xinjiang, as well as the data of SEMs collected from the high dry heat typical environmental test base, were utilized to verify the effectiveness of the method proposed in this paper. The research results not only provide a theoretical basis for solving the reliability evaluation of small sample multiple competitive failure products, but How to carry out the research on the life and reliability of smart electricity meters (SEMs) with the help of typical environmental test bases is a hot and challenging issue in the current industry. In view of the problems of a small amount of failure time, sudden failure and degradation failure of SEMs in the typical environment test base of high dry heat, the classical and Bayes evaluation methods of SEMs reliability are constructed considering the random truncation of the fault data. The reliability information of SEMs in the field operation is combined with the reliability information of SEMs in the typical environment test base of high dry heat to expand the information content and improve the accuracy of SEMs reliability evaluation. Further, considering the multi-index and degradation failure of the metering performance of SEMs, a comprehensive evaluation method of the reliability of SEMs is constructed based on the multivariate Wiener process with competitive failure modes under high dry heat environment, and the point estimates and confidence limits of the three reliability indicators of SEMs are given, including reliability, MTBF and reliable life. The on-site grid- connected operational data from Turpan, Urumqi, and Altay regions in Xinjiang, as well as the data of SEMs collected from the high dry heat typical environmental test base, were utilized to verify the effectiveness of the method proposed in this paper. The research results not only provide a theoretical basis for solving the reliability evaluation of small sample multiple competitive failure products, but